CD39+ Regulatory T Cells Attenuate Lipopolysaccharide-Induced Acute Lung Injury via Autophagy and the ERK/FOS Pathway - Chen, Cen; Li, Xinying; Li, Chuling; Jin, Jiajia; Wang, Donghui; Zhao, Yuan; Gu, Yanli; Chen, Meizi; Zhu, Suhua; Liu, Hongbing; Lv, Tangfeng; Zhang, Fang; et al. (Frontiers in Immunology, 2021)
Acute respiratory distress syndrome (ARDS) is characterized by an uncontrollable cytokine storm, which is associated with high mortality due to lack of effective treatment. Regulatory T cells (Tregs) play an indispensable role in maintaining immune homeostasis and CD39 is considered as a functional cell marker of Tregs. In this study, we aimed to evaluate the effect of CD39+ Tregs on acute lung injury (ALI) and investigate the frequency of CD39+ Tregs in ARDS patients. We found that after lipopolysaccharide (LPS) treatment, CD39-/- mice exhibited more severe inflammation and wild type (WT) mice exhibited a decreased frequency of CD39+ Tregs in the peripheral blood. Furthermore, CD39+ Tregs had a protective effect on LPS-induced inflammation in vitro and the adoptive transfer of CD39+ Tregs had a therapeutic effect on ALI in vivo. We further sought to explore the mechanisms that affect CD39 expression on Tregs. LPS-induced inflammation in the lung impaired the immunosuppressive effect of Tregs via the autophagy-mediated downregulation of CD39. In addition, CD39 induced the expression of itself in Tregs via activating the ERK1/2-FOS pathway. Consistent with this finding, the frequency of CD39+ Tregs was also decreased in the peripheral blood of ARDS patients and was positively correlated with disease severity. Our results suggested that the adoptive transfer of CD39+ Tregs may provide a novel method for the clinical prevention and treatment of ARDS.